The mediating role of sleep quality in the relationship between workload and employees’ job stress: A systematic review - Liwingston Filemon Mona; Iskim Luthfa; Muh Abdurrouf; Dwi Heppy Rochmawati (School of Health Sciences Al-Ma'arif, 2026)
Background: Workload is a major occupational factor that contributes to employees’ job stress and may also impair sleep quality. Increasing evidence suggests that sleep quality is not merely an outcome of work strain, but may function as an important mechanism through which workload influences psychological well-being. However, the mediating role of sleep quality in the relationship between workload and employees’ job stress has not been systematically synthesized across occupational settings. Objective: This systematic review aimed to examine the mediating role of sleep quality in the relationship between workload and employees’ job stress and to synthesize current evidence on how sleep quality explains or modifies this association across employee populations. Methods: This study employed a systematic review design. Literature searches were conducted in Scopus, PubMed, ScienceDirect, ProQuest, and ClinicalKey for Nursing for articles published between 2015 and 2025. Studies were included if they involved employees or workers, examined workload or work-related stress, assessed sleep quality, and reported job stress-related outcomes. Study selection, data extraction, and quality appraisal were conducted systematically, and the findings were synthesized narratively because of heterogeneity in study designs, measures, and analytical approaches. Results: The search identified 2,264 records, and 12 studies were included in the final synthesis. The included studies consistently showed that higher workload or work-related stress was associated with poorer sleep quality across diverse occupational groups. Sleep quality emerged as a recurrent mediating factor linking occupational burden with adverse outcomes, including burnout, depressive symptoms, daytime dysfunction, and reduced well-being. Additional psychological mechanisms, such as rumination, anxiety, and depression, frequently strengthened this pathway, whereas physical activity, resilience, and social support appeared to buffer the negative effects. Conclusion: Sleep quality plays a significant mediating role in the relationship between workload and employees’ job stress. Interventions to reduce job stress should therefore address not only workload management, but also sleep health and related psychological factors in the workplace.